2018
DOI: 10.1038/s41598-018-31209-8
|View full text |Cite
|
Sign up to set email alerts
|

Antrodia cinnamomea boosts the anti-tumor activity of sorafenib in xenograft models of human hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) has been recognized worldwide as one of the major causes of cancer death. The medicinal fungus Antrodia cinnamomea (A. cinnamomea) has been served as a functional food for liver protection. The aim of the present study was to investigate the potential activity of A. cinnamomea extracts as a safe booster for the anticancer activity of sorafenib, a multi-kinase inhibitor approved for the treatment of HCC. The biologically active triterpenoids in the ethanolic extracts of A. cinnamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Antcin-H, a type of triterpene isolated from Antrodia cinnamomea, was reported to inhibit proliferation and migration of human renal carcinoma 786-O cells by targeting MMPs and TIMPs (10). Furthermore, recent articles (12,13,16) revealed that EEA enhances chemosensitivity of several carcinomas, indicating that EEA can be used as adjuvant treatment combined with conventional chemotherapy. Several investigations have already shown the synergistic effects of EEA combined with cisplatin (16), sorafenib (12), and tamoxifen (13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Antcin-H, a type of triterpene isolated from Antrodia cinnamomea, was reported to inhibit proliferation and migration of human renal carcinoma 786-O cells by targeting MMPs and TIMPs (10). Furthermore, recent articles (12,13,16) revealed that EEA enhances chemosensitivity of several carcinomas, indicating that EEA can be used as adjuvant treatment combined with conventional chemotherapy. Several investigations have already shown the synergistic effects of EEA combined with cisplatin (16), sorafenib (12), and tamoxifen (13).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent articles (12,13,16) revealed that EEA enhances chemosensitivity of several carcinomas, indicating that EEA can be used as adjuvant treatment combined with conventional chemotherapy. Several investigations have already shown the synergistic effects of EEA combined with cisplatin (16), sorafenib (12), and tamoxifen (13). The antitumor effect of EEA has been confirmed in a randomized controlled study, although the synergistic effects of EEA combined with chemotherapy were not observed (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vivo study demonstrated that Sorafenib plus EAC greatly decreased tumor growth in nude mice than sorafenib or EAC treatment alone. All this suggest that combined treatment of EAC and sorafenib suppressed HCC tumor growth and could be a possible adjuvant curative approach to treat Hepatocellular carcinoma (HCC) (Wu et al, ).…”
Section: Biological Activitiesmentioning
confidence: 99%